2004
DOI: 10.1038/ni1126
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of IFN-α-induced STAT1 activation and inflammatory function by Syk and ITAM-containing adaptors

Abstract: A key function of interferons is priming multiple cell types for enhanced activation by cytokines and inflammatory factors, including tumor necrosis factor, bacterial lipopolysaccharide and interferons themselves. Here we show that interferon-alpha (IFN-alpha)-induced activation of the transcriptional activator STAT1 and inflammatory STAT1 target genes was enhanced in IFN-gamma-primed macrophages. Enhanced IFN-alpha signaling and proinflammatory function were dependent on the tyrosine kinase Syk and on adaptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 58 publications
4
79
1
1
Order By: Relevance
“…However, entry through the activating FcγR pathway would pose no replicative benefit to DENV unless it is able to overcome the ITAM-Syk-STAT-1 signaling axis that leads to ISG induction (7,13). The findings here thus indicate that coligation of LILRB1 is a critical first step for successful antibody-dependent DENV infection (SI Appendix, Fig.…”
Section: Discussionmentioning
confidence: 83%
“…However, entry through the activating FcγR pathway would pose no replicative benefit to DENV unless it is able to overcome the ITAM-Syk-STAT-1 signaling axis that leads to ISG induction (7,13). The findings here thus indicate that coligation of LILRB1 is a critical first step for successful antibody-dependent DENV infection (SI Appendix, Fig.…”
Section: Discussionmentioning
confidence: 83%
“…Priming with IFN-␥ increased the levels of IFN-␣-induced STAT1 homodimers or ISGF3 but decreased IFN-␥-induced STAT1 ho- modimers (16). Tassiulas et al (25) showed that a high level of STAT1 was not sufficient to enhance IFN-␣-induced STAT1 activation and gene expression after IFN-␥-priming, but the tyrosine kinase Syk and immunoreceptor tyrosine activation motifs were required. In clinical data, the expression level of STAT1 does not influence the response to IFN-␣ adjuvant therapy for cancer patients, and STAT1 levels were even greater in recurrent tumors compared with original tumors (26).…”
Section: Discussionmentioning
confidence: 99%
“…First, because ISGs are genes that should be inducible by IFN-I, such as IFN-a treatment, we filtered the ISGs, which exhibited .4-fold increase in expression in response to IFN-a treatment, based on publically deposited microarray data (Gene Expression Omnibus ID E-GEOD-1740, Fig. 1A, x-axis) (25). Second, the disease-related regulatory ISGs should be more significantly upregulated in progressors than in nonprogressors.…”
Section: Identification Of Hiv-1 Disease-associated Regulatory Isgsmentioning
confidence: 99%